Comportamento de cidadania organizacional: sua interação com os valores organizacionais e a satisfação no trabalho - Costa, Vívian Flores (2014)
This study was developed in order to analyze the influence of organizational values and job satisfaction in organizational citizenship behaviors (OCB), considering the perception of employees and managers. To do so, we performed a descriptive, quantitative and qualitative nature, achieved through a case study of a manufacturer of home appliances. Initially, the quantitative stage involved 302 employees belonging to different hierarchical positions researched Company, who answered a questionnaire from models Scale of Civility in Organizations from Porto and Tamayo (2003), Inventory of Organizational Values Profile from Oliveira and Tamayo (2004) and Job Satisfaction Scale from Siqueira (1995). In a second step, the qualitative stage, 10 managers of Company investigated participated, with whom semi-structured interviews were conducted, the protocol being drawn up in the light of the models used. The main results state that, with respect to the OCB, the behaviors of the Protection system and Cooperation with colleagues were nominated by employees and managers as the most gifts in the organizational context investigated. However, in view of employees, the Self-training and Suggestions organizational management are less practiced in the workplace, however, the vision of managers presented some dissension, as indicated in these behaviors as recurring in members of the organization. In the analysis related to organizational values, identified that, according to the perceptions of employees and managers, are in the Company‟s priority the Dominion and compliance and Prestige and achievement, while values Well-being and Autonomy occupied seats lower in the hierarchy. In relation to job satisfaction, the evaluation of employees and managers showed greater contentment with the dimensions Satisfaction with leadership and Satisfaction with colleagues, and on the other hand, dissatisfaction mustered with Satisfaction with pay and promotions. Still, multiple regression analyzes revealed that the model with greater explanatory power was represented by the variable Creating favorable climate to the organization in the external environment, whose variance explained was 40.4 % by values Prestige and achievement and by the factor Satisfaction with pay and promotions, followed by the Protection system model in which the variance was explained for 31.1% by the values Prestige and achievement and Dominion and compliance and by the factor Satisfaction with colleagues. Thus, it was demonstrated that the organizational values and job satisfaction influence on organizational citizenship behavior.